PENGARUH INTELLECTUAL CAPITAL DALAM KINERJA KEUANGAN DAN NILAI PERUSAHAAN (Studi Empirik Pada Perusahaan Industri Sektor Konsumsi Yang Go Public Di Bursa Efek Indonesia Tahun 2008-2012) - Laurensia Tara (Business Accounting Review, 2015)
Initial study aimed to analyze the influence Intellectual Capital on Financial Performance and Value of the go public Industry Sector Consumption In Indonesia Stock Exchange of 2008-2012 . The independent variable the used was VAIC, while the dependent variable were the Company's financial performance and company value. The data analysis technique used was Regression analysis with Program SPSS Statistics. The Results showed that VACA , VAHU And STVA significantly affect the dependent variables is ROA , ROE , ATO , SG , TOBINS'Q and PER . FOR t test only VACA had dominant influence Against Corporate Profitability to Both dependent ROA and ROE. While the dominant influence Against The productivity variable were the dependent variable VAHU either ATO or SG , and the dependent variable of  Company Value VAHU variables had significant affect on TOBINS'Q And STVA variables affect significantly on PER .